Efektivitas Konseling Kelompok dalam Meningkatkan Self Efficacy Melalui Pendekatan Cognitive Behavior Therapy - Amelia Putri; Salbiyah Salbiyah; Mardhotillah Mardhotillah; Raul Rian Shaputra; Ratna Sari Dewi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Self-efficacy is an individual's belief in their ability to face challenges and achieve goals. In guidance and counseling, self-efficacy is an important factor that affects individual development. One effective method to improve self-efficacy is group counseling with the Cognitive Behavioral Therapy (CBT) approach. This approach focuses on changing negative thought patterns, increasing self-confidence, and strengthening individual skills through social support in groups. This study uses the literature review method to analyze the effectiveness of CBT-based group counseling in improving self-efficacy. The results showed that CBT-based group counseling provides a supportive environment for individuals to share experiences, obtain social support, and learn from other group members. Through this process, individuals can increase their self-confidence, develop social skills, and form a more positive mindset. In addition, CBT also helps individuals manage their emotions, cope with stress, and increase their resilience in facing life's challenges.